THE USE OF COHESIVE DEVICES IN ENGLISH EDUCATION STUDENTS' WRITINGS - Putra, Galih Eka (2016)
This study discovers how cohesive devices used in twelve students' writing written by four students - two high achiever learners and two low achiever learners - of English Education Program in Indonesian University. With the characteristics of case study approach, the research study applies a qualitative method research design and employs Halliday and Hasan's (1976) taxonomy of cohesion framework as a ground theory and a tool for text analysis. The findings show that grammatical cohesive devices are used slightly more frequent than the lexical ones. The students frequently used reiteration followed by reference, conjunction, collocation, substitution, and ellipsis with two general functions; to remind the readers about the topic discussed and to show the position of the author within the text. Furthermore, it is realized that to some extent, the way students use cohesive devices is a little bit different; in which at the final point, high achiever learners tend to use more various cohesive devices than the low ones in maintaining their quality of writing. Keywords: Cohesion, Cohesive Devices, Writing Quality Penggunaan Perangkat Kohesif di Tulisan-tulisan Mahasiswa Pendidikan Bahasa Inggris Penelitian ini mengemukakan bagaimana perangkat kohesif digunakan pada dua belas tulisan buatan empat mahasiswa - dua siswa berprestasi tinggi dan dua siswa berprestasi rendah - jurusan pendidikan bahasa inggris di salah satu universitas di Indonesia. Dengan karakteristik pendekatan studi kasus, penelitian ini menerapkan metode kualitatif dan menggunakan taksonomi kerangka kohesi yang diusung Halliday dan Hasan (1976) sebagai teori dasar dan alat untuk menganalisis teks. Temuan menunjukan bahwa perangkat kohesif gramatikal digunakan sedikit lebih sering daripada yang leksikal. Para siswa seringkali menggunakan reiteration diikuti oleh reference, conjunction, collocation, substitution, dan ellipsis dengan dua fungsi umum; untuk mengingatkan pembaca tentang topic yang sedang dibahas dan untuk menunjukan posisi penulis didalam teks. Selanjutnya, disadari bahwa pada titik-titik tertentu, cara siswa menggunakan perangkat kohesif sedikit berbeda; yang mana pada akhirnya, siswa yang berprestasi tinggi cenderung menggunakan perangkat kohesif yang lebih variatif daripada yang digunakan oleh siswa yang berprestasi rendah dalam mempertahankan kualitas tulisannya. Kata Kunci: Kohesi, Perangkat Kohesif, Kualitas Tulisan